Noise exposure levels and hearing loss risk among music major students - Tey, Ming Luan; Chan, Cheong Jan; Hood, Made Mantle (Faculty of Music and Performing Arts, Universiti Pendidikan Sultan Idris, 2014)
Assessment of noise exposure levels and hearing loss among professional musicians has been conducted in various settings such as classical orchestral concerts and rehearsals in concert halls and orchestra pits; rock, jazz or pop live concerts and gigs over the past 40 years. Despite numerical measurements of noise exposure levels among professional musicians and the convincing evidence of musicians are in high risk of hearing loss, both as soloist or in ensemble, there are few noise studies that focus specifically on music major students. The general objective of this study aims at providing a general evaluation on the noise exposure level and risk of hearing loss among music major students. This particular paper, however, present the result of exploratory stage where the result of a single piano student will be focused. A docimeter was used to detect the noise exposure level of the student in a daily routine, which includes their personal practice time, ensemble practice time and examination time in different rooms and examination halls. An audiometric test was also conducted to provide insights into the potential risk of hearing loss. Based on the results, this paper discuss the need to examine music major students’ noise exposure level and their hearing capacities.